Step-by-step explanation
Finding the product of the given functions.
The product of two functions is defined as follows:
![(f\cdot g)(x)=(f)(x)\cdot(g)(x)](https://img.qammunity.org/2023/formulas/mathematics/college/414c7b3yyh8jdikgwgxifgi4oetdeuamtc.png)
Then, we have:
![\begin{gathered} f(x)=(6)/(x+7) \\ g(x)=x+5 \\ (f\cdot g)(x)=(f)(x)*(g)(x) \\ (f\cdot g)(x)=(6)/(x+7)(x+5) \\ (f\cdot g)(x)=(6(x+5))/(x+7) \\ (f\cdot g)(x)=(6x+30)/(x+7) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/owojyfjpalfj9gi4236ytth1e5s9yqkxbe.png)
Finding the domain of f · g
Step 1: We set the denominator equal to 0 to find where the above expression is undefined.
![x+7=0](https://img.qammunity.org/2023/formulas/mathematics/college/reb7er0lc1321ncjx2hzc4tei2konyxoex.png)
Step 2: We subtract 7 from both sides.
![\begin{gathered} x+7-7=0-7 \\ x=-7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qi9d08zlomukj7lq98sobyvlu6oaqvh87g.png)
Step 3: Since the domain is all values of x that make the expression defined, the domain of f · g is all values of x different from -7.
![\begin{gathered} D={}{}\lbrace x|x\\e-7\rbrace \\ \text{ or} \\ D=(-\infty,-7)\cup(-7,\infty) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lu9vgks1k38mff7tqrsfl87upaclkypfda.png)
Answer
![D=(-\infty,-7)\cup(-7,\infty)](https://img.qammunity.org/2023/formulas/mathematics/college/v0v8j8ml3wc9vk2ycgi2ru8zkthm4xv3n6.png)